Edukasi Praktik Akad-Akad Syariah Di Sekolah Luar Biasa Negeri Bangkinang - Assyifa, Zubaidah; Mairiza, Diany; Rahmawati, Rahmawati; Irmawanti, Irmawanti; Delia, Dwi Anisa (EL-EMIR INSTITUTE, 2025)
This community service activity was carried out in Kampar Regency, Riau Province, with the target of the program being the State Special Needs School (SLBN) in Bangkinang Kota District. The main objective of this activity was to introduce and socialize the practice of Sharia contracts (akad) to students with special needs at the school. The program was designed to help students understand the basic principles of Islamic economics through a simple and interactive approach. The results showed positive outcomes, marked by the achievement of the targeted number of participants, fulfillment of the program’s objectives, completion of the planned material, and the participants’ ability to comprehend the content delivered. Furthermore, the success of this activity was also reflected in the high enthusiasm and satisfaction of the participants. The facilitators provided clear explanations, allowed sufficient time for questions, and the students were able to respond well to the questions asked. The main benefit gained by the participants was improved knowledge and understanding of Islamic economic principles, particularly those related to Sharia contracts.